Cultura e responsabilidade social empresarial : uma análise das ações culturais de responsabilidade social empresarial - o caso da Petrobras e do grupo Votorantim - Belem, Marcela Purini (2010)
This essay analyzes the interface between culture and corporate social responsibility, performing an analysis of the investment in Culture made by Petrobras and Grupo Votorantim. The aim of this paper is to analyze the interface between the financing of Culture and Corporate Social Responsibility. To accomplish this task, we analyzed two large national companies. Petrobras, as this is the company that most sponsors cultural projects in Brazil and Grupo Votorantim as counterpoint.